China man - Chow, Jerrell Zhi Hong (2019)
At the age of five, Ek Kiat left his family and village in China to be adopted by new parents in Singapore. This drastic transition led to a troubled childhood, as he grew up with the self-inflicted pressure to suppress his past. China Man, a 24-minute documentary short, follows Ek Kiat as he confronts the deep-seated insecurities that have plagued him the past 20 years.